IDENTIFICATION OF THE OBJECTS BASED ON THE ANALYSIS OF THE MAGNETIC SIGNATURES - J; M (Интеллектуальные системы в производстве, 2009)
The measuring, control and evaluation system for measuring and analysis of the magnetic signatures of objects is described in this article. A first part of the article is focused on the measuring system based on sensor HMR2300. A second part of the article contains a description of the control and evaluation system for analysis of the measured sensor data. At the conclusion of the article an experiences and improvement tips concerned with measurement system are presented.